Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1089/neu.2015.4287
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Quality of Life after Brain Injury Scores: Cross-Walk with the Short Form-36

Abstract: The Quality of Life after Brain Injury (QOLIBRI) instruments are traumatic brain injury-specific assessments of health-related quality of life (HRQoL), with established validity and reliability. The purpose of the study is to help improve the interpretability of the two QOLIBRI summary scores (the QOLIBRI Total score and the QOLBRI Overall Scale score). An analysis was conducted of 761 patients with traumatic brain injury (TBI) that took part in the QOLIBRI validation studies. A cross-walk between QOLIBRI scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 18 publications
3
52
1
Order By: Relevance
“…Our cohort of patients had higher average PCS scores (M = 52.46, SD ± 19.46) compared to MCS (M = 51.77, SD ± 25.60). This is in agreement with results of the study by Steinbuechel et al, Hawthorne et al and Wilson et al [ 20 , 36 , 41 ]. In contrast, other studies found reverse results with subjects having higher MCS than PCS [ 15 , 17 , 21 , 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our cohort of patients had higher average PCS scores (M = 52.46, SD ± 19.46) compared to MCS (M = 51.77, SD ± 25.60). This is in agreement with results of the study by Steinbuechel et al, Hawthorne et al and Wilson et al [ 20 , 36 , 41 ]. In contrast, other studies found reverse results with subjects having higher MCS than PCS [ 15 , 17 , 21 , 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…Comparing major TBI with no or mild TBI patients 20.8% ( n = 22) and 18.5% ( n = 17), respectively, presented with a total QOLIBRI of < 60 ( p = 0.690) and were defined as having an impaired HRQoL according to Wilson [ 38 ]. 27.0% ( n = 27) achieved an SF-36 mental (MCS) < 40 ( p = 0.629) and were considered conspicuous.…”
Section: Resultsmentioning
confidence: 99%
“…Proxy completion is impossible for many QOLIBRI items and misses the essence of measuring the “self-perceived” HRQoL. It also remains unclear whether the cut-off point of 60 is satisfying for quantifying a good HRQoL [ 49 ]. Therefore, validity should be confirmed for patients with TBI-associated persisting cognitive restraints or suitable new (HRQoL) measurement options need to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Scores are transformed to total scores ranging from 0 (worst possible quality of life) to 100 (best possible quality of life) [ 46 ]. A score lower than 60 is believed to represent a low or impaired HRQoL [ 49 ]. In case patients did not return the questionnaire, the investigators attempted a telephone interview, or family members were asked to assist in completing the forms.…”
Section: Methodsmentioning
confidence: 99%